A Global Politics of Pity? Disaster Imagery and the Emotional Construction of Solidarity after the 2004 Asian Tsunami1. Issue 1 (21st March 2014) - Hutchison, Emma
Abstract : The study of emotion has become a steadily growing field in international relations and international political sociology. This essay adds to the field through a further empirical examination of the political roles emotions can play. Specifically, the essay questions how emotions were implicated in the construction of transnational solidarity—and the associated humanitarian actions—following an event of pivotal global importance: the Asian tsunami disaster of December 2004. To this end, I focus on the emotional dimensions of dominant media tsunami imagery and examine how emotions helped to produce the humanitarian meanings and ideologies on which the subsequent solidarity and humanitarian actions were based. Analyzing photographs in the New York Times, the essay demonstrates that the dominant tsunami imagery helped to evoke solidarity and garner aid. It did so, at least in part, through mobilizing stereotypical and deeply colonial representations of developing world disaster that are suggestive of a "politics of pity." In this way, the essay contributes both an empirical study of emotions in world politics and an examination of the linkages between emotions and contemporary humanitarianism.